2005
DOI: 10.1021/om0400907
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Silicon-Bridged Benzocrown Ethers and Their Ionochromism in the Emission Spectra Arising from Intramolecular π−π Stacking

Abstract: Compounds having two benzocrown ether units bridged by a mono-, di-, or trisilanylene unit were prepared, and ionochromic effects on their optical properties were studied. Of these, disilanylene- and trisilanylene-bridged ones exhibited clear ionochromism in the emission spectra and the intensity of the original emission band at about 320 nm decreased and a new broad band centered at 400 nm appeared when appropriate alkali or alkali-earth metal ions were added into the acetonitrile solutions. In contrast, a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…Here, we report the synthesis and iono- and solvatochromic behaviors of poly(silylene- p -phenylene)s having a benzo crown ether group as the pendant group, which is anticipated to interact with metal ions more tightly than linear ether side chains. In these polymers, electron-donating silyl substitution on the benzo crown unit would even facilitate the coordination to the metal ions . As expected, the polymers exhibited clear ionochromism in the emission spectra toward selected alkali-metal and alkaline-earth-metal ions, depending on the ring size of the crown ether.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Here, we report the synthesis and iono- and solvatochromic behaviors of poly(silylene- p -phenylene)s having a benzo crown ether group as the pendant group, which is anticipated to interact with metal ions more tightly than linear ether side chains. In these polymers, electron-donating silyl substitution on the benzo crown unit would even facilitate the coordination to the metal ions . As expected, the polymers exhibited clear ionochromism in the emission spectra toward selected alkali-metal and alkaline-earth-metal ions, depending on the ring size of the crown ether.…”
Section: Introductionsupporting
confidence: 62%
“…Recently, we found that disilanylene- and trisilanylene-bridged benzo crown derivatives shown in Chart exhibited ionochromic behaviors responding to alkali and alkaline-earth- metals . However, in contrast to the present polymers, the silanylene-bridged benzo crown derivatives showed the emission maximum at about 320 nm in the absence of metal ions; addition of metal ions to the solutions led to a decrease of the emission intensity of the original band, together with enhancement of a new broad band centered at 400 nm.…”
Section: Resultsmentioning
confidence: 61%
“…Recently, investigation of oligosilyl derivatives represents a significant challenge to understand the photophysical properties due to the effective σ–π conjugation through Si–Si bonds. Especially, diaryldisilanes are promising as soft crystals driven from the conformational variety and flexibility of Si–Si σ-bonds. Previously, we reported that the donor–acceptor disilane 1 (Figure ) displayed second harmonic generation (SHG) in the crystalline state, which is widely used in advanced photonic technologies. This compound has a strong transition dipolar moment by a strong donor moiety (−NMe 2 ) and an acceptor moiety (−CN) with Si–Si σ-conjugated linker, showing no absorption in the visible light region different from a large π-extended skeleton.…”
Section: Introductionmentioning
confidence: 99%